Cyber Law Analysis and Customer Protection in Cases of Phishing in Digital Banking - Maria Minerva Gani; Cheryl Nathania; Heigel Parodi Ritonga; Nathasya Jhonray Siregar; Rifaldo Aditya; Putra Dirgantara; Nicole Eugenia Yuri; Tasya Amira F Siregar (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This study examines phishing in digital banking services as a form of cybercrime that combines electronic system manipulation and social engineering. Phishing is not merely a technical security issue, but also a legal problem involving criminal liability, consumer protection, and personal data protection. This research uses normative legal research with statutory and case approaches, particularly by analyzing phishing practices involving fake banking websites that resemble official digital banking platforms. The findings show that phishing can be legally constructed through several provisions under the Electronic Information and Transactions Law, the Personal Data Protection Law, and the National Criminal Code. The perpetrator’s liability may be established through the elements of unlawful act, intent, capacity to be held responsible, and the absence of justifying or excusing grounds. In addition, victim protection must be carried out through preventive measures, responsive handling, and recovery mechanisms, including strengthening digital security, improving customer literacy, conducting internal investigations, and providing dispute resolution channels. Therefore, the prevention and handling of phishing in digital banking requires an integrated approach that combines criminal enforcement, banking governance, consumer protection, and personal data protection.